The Influence of Religion Over Family Planning: the Case of the Republic of Macedonia - Chavdar, Kimo; Andeva, Marina; Kedeva, Karolina (European Scientific Journal, ESJ, 2017)
Religions have been dominant for thousands of years in each and every aspect of human life, particularly in the domain of the family communion. The influence of religion as a specific form of collective consciousness, and as a system of moral rights and norms, since their appearance until today, is particularly interesting for the Republic of Macedonia. In this small territory, despite the fact that a variety of different religious communities have coexisted throughout the centuries, yet there is a major difference in the approach of family planning customs. This is mostly evidenced in the cases of the population representing the Orthodox Christian and Muslim religions. In this article we elaborate, firstly the viewpoints on family planning and reproduction of the Orthodox Christian and Muslim religions as the dominant religions in the Republic of Macedonia and discuss viewpoints and attitudes towards family planning (abortion) among the Macedonian citizens.